Morphological determination of the larval instars of Eupeodes americanus (Diptera: Syrphidae) - Fauteux, Arlette; Gonzalez, Noémie; Soares, António; Lucas, Éric (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2022)
In North America, the potential of the American hoverfly Eupeodes americanus (Wiedemann, 1830) (Diptera: Syrphidae) as a biocontrol agent has been demonstrated, particularly against the foxglove aphid Aulacorthum solani Kaltenbach, 1843 (Hemiptera: Aphididae). Since no information is available to distinguish the larval instars of this species, the present study used the semi-continuous observation (time-lapse photography and stereo microscope) of the three larval stages to build a table of morphological traits and a dichotomic key for discriminating the larval instars by observation under stereo microscope. Discriminating traits are black hairs at first instar and fused posterior breathing tubes at third instar.